Analisis Penguasaan Konsep Kekuatan Asam Basa Hasil Pembelajaran Model Problem Based Learning Berbantuan LKS-Deduktif - Haliza, Nur; Sadiana, I Made; Meiliawati, Ruli (FKIP Universitas Palangka Raya, 2024)
Mastery of the concept of acidity (pH) can be achieved when students are directly involved in applying their knowledge. The purpose of this study is to describe students' concept mastery as a result of learning through the implementation of the problem-based learning model assisted by guided deductive worksheets (LKS-Deduktif) on the topic of acid-base strength in Class XI MIPA 4 at SMA Negeri 3 Palangka Raya. This research is descriptive in nature, and the subjects are students of Class XI MIPA 4. The instruments used in the study include a concept mastery test consisting of pretest, posttest, and guided deductive worksheets (LKS-Deduktif). The implementation stages include administering a pretest, guided deductive worksheets, and finally a posttest. The results show that the problem-based learning model assisted by guided deductive worksheets in Class XI MIPA 4 led to an increase in concept mastery from 5.35% to 98.18%, categorized as excellent. The improvement in student mastery produced an N-gain score of 0.98, categorized as high. The number of students mastering each conceptual label is as follows: (1) Calculating the pH of strong acid solutions based on concentration data: 100%. (2) Calculating the pH of strong base solutions based on concentration data: 100%. (3) Analyzing the pH comparison of weak acid solutions based on concentration data and acid dissociation constant (Ka): 96.6%. (4) Analyzing the pH comparison of weak base solutions based on concentration data and base dissociation constant (Kb): 96.2%.